Effects of Sexual Harassment on Learning Activities and Coping Strategies among University Girl Students - Gyawali, Kalpana; Karki, Sarasawati (ILAM इलम, 2023)
The aim of this research was to explore the impact of sexual harassment on the academic activities of female students at Tribhuvan University and their strategies for dealing with harassers. The study employed a qualitative approach, using focus group discussions and in-depth interviews to gather data. The researchers organised the students' narratives to analyse the findings. The study revealed that various learning activities were negatively affected by sexual harassment among female students. These included difficulties in memorization, incomplete assignments, problems with presentations, a reluctance to ask questions or participate in group discussions, a sense of disorientation, disturbances, fear, and a loss of motivation. The coping mechanisms employed by the victims included avoiding the harasser, reprimanding them, confiding in friends and siblings, and lodging verbal complaints with the school principal and administrative authorities. However, due to limited trust in the institution, the lengthy legal process, and the fear of being accused themselves, legal action against the harassers was not commonly pursued.